A pilot study showing a stronger H1N1 influenza vaccination response during pregnancy in women who subsequently deliver preterm. (April 2019) - Andorf, Sandra; Bhattacharya, Sanchita; Gaudilliere, Brice; Shaw, Gary M.; Stevenson, David K.; Butte, Atul J.; Sirota, Marina
Graphical abstract: Highlights: Women who go on to deliver preterm have a greater flu vaccine response for the H1N1 strain than. women who delivered at term. No difference was observed for H3N2. An increased activation of the maternal immune system might be linked to preterm birth. Abstract: Problem: Preterm birth (PTB), or the delivery of an infant prior to 37 weeks of gestation, is a major health concern. Although a variety of social, environmental, and maternal factors have been implicated in PTB, causes of preterm labor have remained largely unknown. There is evidence of effectiveness and safety of influenza vaccination during pregnancy, however fewer studies have looked at vaccination response as an indicator of an innate host response that may be associated with adverse pregnancy outcomes. We carried out a pilot study to analyze the flu vaccine response during pregnancy of women who later deliver preterm or term. Method of study: We performed a secondary analysis of the individual-level data from an influenza vaccination response study (openly available from ImmPort) measured by hemagglutination inhibition assay of 91 pregnant women with term deliveries and 11 women who went on to deliver preterm. Flu vaccination responses for H1N1 and H3N2 influenza strains were compared between term and preterm deliveries. Results: Women who went on to deliver preterm showed a significantly ( P  <  0.001) greater flu vaccine response for the H1N1 strain than women who delivered at term. The vaccine response for H3N2 was not significantly different between these two groups ( P  =  0.97). Conclusions: Although the sample size is limited and additional validation is required, our findings suggest an increased activation of the maternal immune system as shown by the stronger vaccination response to H1N1 in women who subsequently delivered preterm, in comparison to women who delivered at term.